Investigating translational motion of a dual friction-drive surface acoustic wave motor through modeling and finite element simulation. (February 2019) - Behera, Basudeba; Nemade, Harshal B
This study presents the investigation of translational motion of a surface acoustic wave (SAW) linear motor employing dual friction drive (DFD) through mathematical modeling and finite element simulation. The presented SAW linear motor consists of two identical piezoelectric stators facing each other and holding a slider tightly between them. The slider is placed in the path of SAWs generated in the two stators supplied with the preload required for the friction drive, which is capable of moving the slider in forward and reverse translational motion. Typically, the stator contains an interdigital transducer (IDT) fabricated on either side of a lithium niobate (LiNbO3 ) substrate so that the application of sinusoidal voltage excitation to an IDT generates a traveling Rayleigh SAW on the surface of the substrate. The SAW, in the presence of preload, interacts with the slider and the frictional force drives the slider. By simultaneously exciting two IDTs, one each from the top and bottom stators, on one side of the motor, the slider makes a translational motion toward the side of the activated IDTs. The direction of the movement of the slider can be reversed by switching excitation to the IDT pair on the particular side of the motor. Mathematical modeling and finite element simulation of the motor is carried out to study the characteristics such as step motions, displacement, and forces acting on the slider for different amplitudes of input excitation. Finally, a comparative study has been carried out to show the advantages of the proposed DFD SAW motor over the conventional SAW motor.